Synthesis, characterization, X-ray crystal structure and Hirshfeld surface analysis of Ni(II) complex of 1,2-bis(pyridin-2-ylmethylene)hydrazine - Sahu, Meman; Manna, Amit Kumar; De, Dinesh; Patra, Goutam Kumar (European Journal of Chemistry, 2022)
We report the synthesis, characterization, X-ray crystal structure and Hirshfeld surface analysis of Ni(II) perchlorate complex (1, Ni2L3·4ClO4·2CH3CN) of 1,2-bis(pyridin-2-ylmethylene)hydrazine (L) ligand. The X-ray crystallographic study of complex 1 reveals that in the presence of Ni(II) ions,the ligand L forms a dimeric triple helix with a Ni(II)-Ni(II) distance of 3.794 Å. Crystal data for C40H36Cl4N14Ni2O16: Monoclinic, space group P21/c (no. 14), a = 20.7558(19) Å, b = 13.1937(12) Å, c = 20.0181(18) Å, β = 96.9510(10)°, V = 5441.6(9) Å3, Z = 4, T = 293.15 K, μ(MoKα) = 0.965 mm-1, Dcalc = 1.498 g/cm3, 38075 reflections measured (1.976° ≤ 2Θ ≤ 43.728°), 6557 unique (Rint = 0.0695, Rsigma = 0.0466) which were used in all calculations. The final R1 was 0.0518 (I > 2σ(I)) and wR2 was 0.1270 (all data). The Hirshfeld surface analysis of complex 1 shows that C···H, H···H, N···H and O···H interactions of 10.9, 26.4, 6.7, and 33.4%; respectively, which exposed that the main intermolecular interactions were H···H intermolecular interactions.